Sports administration: an examination of the competitive balance concept through european and brazilian domestic soccer leagues comparison - Levy, Pierre Antoine François (2011)
The issue of Competitive Balance (CB) is a major theme of the economics of professional sports in the United States and Europe. Many researches were made to establish the most relevant criteria when evaluating the competitiveness of professional soccer leagues. This research analyzed the relevance of CB as determinant of competitiveness comparing with the Brazilian soccer league with 9 major leagues in Europe (Belgium, England, Germany, Netherlands, France, Italy, Portugal, Scotland, and Spain). Competitiveness is the ability of a firm (a club) or an industry to face effective or potential competition. The measure of competitiveness should take into consideration a number of significant factors such as quality and value for money, human resources management and business organization. This work is aimed at demonstrating that while uncertainty of outcome have been long considered as a positive factor of attractiveness/fan interest in sports, a balanced league might have a negligible not say negative effects on soccer leagues’ long-term competitiveness. The results showed that increasing CB might be relevant for weakest leagues(Belgium, Netherlands, Portugal, Scotland) but not for the top G5 (Germany, Spain, France, England, Italy). Consequently, CB should be contemplated as a negligible variable when considering soccer leagues’ competitiveness despite the growing interest for the concept in literature. Mainly based on the researches of Dell´Osso and Symanski (1991) and Oughton and Michie (2004), the HHI index (Herfindahl-Hirschman) has been used to determine the level of concentration of the 11 soccer leagues studied. A thorough literature review on sports and soccer administration throughout the world was performed.